2019
DOI: 10.1111/jocd.13099
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of moisturizing and irritation potential of sacha inchi oil

Abstract: Objective The moisturizing and irritation effects of sacha inchi oil were evaluated. Study Design The moisturizing effect on the skin was clinically assessed using a regression study design. Sacha inchi oil or olive oil (benchmark) was applied on the left or right lower leg of the subjects for 14 days followed by application discontinuation for 2 days. The TEWL, skin moisture content and dryness appearance were observed. Methods The fatty acid composition and characteristics of cold‐pressed sacha inchi seed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Natural antioxidants, including tocopherols and polyphenol have been found in the oil. The present study, the seedling extracts showed stronger on free radical scavenging which the extract composition with the tocopherols, known as vitamin E is an important minor component in oil that may be antioxidative and slow down the process of oxidation 29 . Moreover, phenolic compounds, flavonoids were detected in seedling extracts that are good for the oil's oxidative stability of polyunsaturated fatty acids imparting the characteristic flavor to the oil.…”
Section: Discussionsupporting
confidence: 51%
“…Natural antioxidants, including tocopherols and polyphenol have been found in the oil. The present study, the seedling extracts showed stronger on free radical scavenging which the extract composition with the tocopherols, known as vitamin E is an important minor component in oil that may be antioxidative and slow down the process of oxidation 29 . Moreover, phenolic compounds, flavonoids were detected in seedling extracts that are good for the oil's oxidative stability of polyunsaturated fatty acids imparting the characteristic flavor to the oil.…”
Section: Discussionsupporting
confidence: 51%
“…Sacha inchi oil has been recognized for its positive antioxidant benefit [ 56 , 57 ]. Moreover, sacha inchi oil has moisturizing and anti-irritation activities [ 21 ]. Populations in the Amazon rainforest, which is the origin of sacha inchi plants, routinely apply sacha inchi oil to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…This plant is native to Peruvian Amazon regions but currently is commercially cultivated around the world. Sacha inchi oil is traditionally used in Peru for skin care because of its moisturizing and anti-irritation potential [ 21 ]. Sacha inchi oil also exhibits antibacterial and anti-inflammation activities [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…DEBORAH GROUP LABORATORIES developed the Gloss Euphoric Shine, a lipstick with a mix of components "that gives an immediate feeling of wellbeing" due to the presence of the nourishing and moisturizing blue poppy extract, omega-6 and -9, vitamins, and the innovative molecule Euphoryl TM Ω3 [49]. This active ingredient is a mix of Sacha inchi oil-rich in omega-3 [50][51][52]-and Schinus terebinthifolia (pink pepper) extract [37,53]. Omega-3 fatty acids help to counteract hypersensitivity, dryness, and inflammation, refining skin appearance, and also have antioxidant properties, thereby helping keep women's skin healthy and glowing.…”
Section: Feelings Of Pleasantness and Wellbeing Vs Neurocosmeticsmentioning
confidence: 99%